Web Development Prototype on Land and Building Tax Revenue Features (Case Study: Bekasi City) - Fauzan, M; Bertalya, Bertalya (International Journal of Computer Sciences and Engineering, 2020)
Bekasi's land and building tax revenue have not yet reached its annual target. This is caused by a bureaucratic complicated warning and payments. The information was obtained from the official body of the city of Bekasi in the form of tax revenue data and interviews. This research contains an official web development feature design for Bekasi city. These features are online land and building tax payments and visualization of tax revenue with Geographic Information Systems. The design was made using the Rapid Application Development method and using UML tools and tested with COBIT 4.1. Activity diagrams and use-case diagrams are used to determine user behavior. The prototype was made with Adobe XD. The COBIT domain used is Delivery and Support, namely DS1, DS4 and DS7. The assessment results show that with the prototype, respondents can understand the information provided, know the stages of payment, and agree that development is needed.